1991
DOI: 10.1007/bf00197950
|View full text |Cite
|
Sign up to set email alerts
|

Ionic currents flow through Micrasterias and Closterium cells during expansion of the primary cell wall

Abstract: The results of studies of Micrasterias rotata (Grev.) Ralfs, M. thomasiana Archer (biradiate and uniradiate forms) and Closterium sp. using one- and two-dimensional vibrating probes show that transcellular ionic currents are detectable only around cells undergoing expansion of the primary cell wall (half-cell); current enters local regions of expansion and exits over both the rigid surface of the secondary wall and regions of the primary wall where hardening of the wall prevents further expansion. Current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…This means that outgrowth of the lobes of a Micrasterias cell occurs only at areas characterized by an accumulation of membrane-associated calcium. These results are supported by recent studies in which one-and two-dimensional vibrating probes were used to measure transcellular ionic currents in growing Micrasterias cells (88)(89)(90). Inward ionic currents that "may be carried at least in part by Ca2 , Cl1, H+ and K+ ions" (89) enter at the local areas of cell expansion and exit at the areas of the cell indentations and at the surface of the nongrowing semicell ( Fig.…”
Section: Distribution and Function Of Membrane-associated Calcium Andsupporting
confidence: 81%
See 1 more Smart Citation
“…This means that outgrowth of the lobes of a Micrasterias cell occurs only at areas characterized by an accumulation of membrane-associated calcium. These results are supported by recent studies in which one-and two-dimensional vibrating probes were used to measure transcellular ionic currents in growing Micrasterias cells (88)(89)(90). Inward ionic currents that "may be carried at least in part by Ca2 , Cl1, H+ and K+ ions" (89) enter at the local areas of cell expansion and exit at the areas of the cell indentations and at the surface of the nongrowing semicell ( Fig.…”
Section: Distribution and Function Of Membrane-associated Calcium Andsupporting
confidence: 81%
“…15). Treatment with Ca2+ channel blockers such as gadolinium results in a decrease of the measured currents (89). Accordingly, elimination studies with different salt solutions (47,97), as well as experiments with ethylene glycol-bis(13-aminoethyl ether)-N,N,N',N'-tetraacetic acid (EGTA) and LaCl2 (45), show that Ca2+ is required for normal completion of morphogenesis at least in trace amounts.…”
Section: Distribution and Function Of Membrane-associated Calcium Andmentioning
confidence: 95%
“…The signal-transduction mechanisms and response cascades are just beginning to be understood in desmids. It has previously been shown that ion currents are quickly set up external to the cell surface (Brower and Giddings 1980, Meindl 1982, Lehtonen 1984, Nawata 1988, Troxell and Scheffey 1991, and that calmodulin and monovalent cation dynamics affect the secretory mechanism in desmids (Domozych 1999, Linde et al 2001). However, it is possible that a thigmotactic system involving rapid electrochemical changes upon the cell surface, which, in turn, initiate a signal cascade involving calcium or sodium channels ⁄ dynamics, is the key in the postadhesion behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise target zones and particular activities of Na + in the plant cell are not well known. Several methods have been employed in studying the role of cations in plant cell physiology including microinjection of cation-specific fluorescent labels followed by confocal-microscopic localization and vibrating-microprobe elucidation of cation-derived electrical currents (Feij6 et al 1995, Nawata 1992, Troxell and Scheffey 1991, Holzinger et al 1995, Hepler and Gunning 1998. Another mode of analysis includes application of specific ion-altering agents followed by microscopic analysis of cellular and biochemical alterations.…”
Section: Introductionmentioning
confidence: 99%